Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Pemerintah Kabupaten Jombang Tahun Anggaran 2014 – 2018 (Studi Kasus Di Pemda Kabupaten Jombang) - Susanti, Hevi; Budiono, Arief; Supriadi, Supriadi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Financial performance analysis in this study is an assessment process regarding the level of progress in achieving the implementation of work/activities of the Regional Government in the financial sector by using tools in the form of financial ratios which consist of: Analysis of Regional Financial Independence Ratio, Analysis of Regional Financial Dependency Ratio, Analysis of Effectiveness of Original Income Ratio Regions, Regional Financial Efficiency Ratio Analysis, Activity Ratio Analysis, Growth Ratio Analysis and Proportion Analysis The purpose of writing this final project is to determine the financial performance of the Government of Jombang Regency in the 2014-2018 Fiscal Year. The data used are primary and secondary data obtained through interviews, observation and literature study. The data obtained were analyzed using quantitative descriptive analysis methods. After analyzing, it can be concluded that the financial performance of the Jombang Regency Government shows the average regional financial performance which is still unstable. Where the results of calculations every year are still experiencing numbers up and down. This is because the Government of Jombang Regency has not been optimal in managing the wealth of available regional resources. However, on the side of revenue achievement, Jombang Regency has demonstrated its ability to achieve Regional Original Revenue beyond the set targets.